Eigenvalue problems with discontinuous eigenfunctions and their numerical solutions - Deineka, V. S.; Sergienko, I. V.; Skopetskii, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider new eigenvalue problems with discontinuous eigenfunctions and construct computational algorithms whose accuracy is not worse than the accuracy of analogous known algorithms for problems with smooth eigenfunctions.